Performance of Stylosanthes hamata cVerano as influenced by nutrient changes - Mohamed-Saleem, M.A.; Otsyina, R.M.; Butterworth, M.H. (1986)
An experiment conducted to assess the nature of nutrient problems with a view to improving the performance of Verano stylo at the ILCA site (Kaduna). Shows the rates of nutrient application, composition and drymatter yields by varying nutrient additions and in two growing seasons. Also shows P and Cu application on Dm yield.